Bmp7 regulates the survival, proliferation, and neurogenic properties of neural progenitor cells during corticogenesis in the mouse. - Aikaterini Segklia (Public Library of Science (PLoS), 2012)
Bone morphogenetic proteins (BMPs) are considered important regulators of neural development. However, results mainly from a wide set of in vitro gain-of-function experiments are conflicting since these show that BMPs can act either as inhibitors or promoters of neurogenesis. Here, we report a specific and non-redundant role for BMP7 in cortical neurogenesis in vivo using knockout mice. Bmp7 is produced in regions adjacent to the developing cortex; the hem, meninges, and choroid plexus, and can be detected in the cerebrospinal fluid. Bmp7 deletion results in reduced cortical thickening, impaired neurogenesis, and loss of radial glia attachment to the meninges. Subsequent in vitro analyses of E14.5 cortical cells revealed that lack of Bmp7 affects neural progenitor cells, evidenced by their reduced proliferation, survival and self-renewal capacity. Addition of BMP7 was able to rescue these proliferation and survival defects. In addition, at the developmental stage E14.5 Bmp7 was also required to maintain Ngn2 expression in the subventricular zone. These data demonstrate a novel role for Bmp7 in the embryonic mouse cortex: Bmp7 nurtures radial glia cells and regulates fundamental properties of neural progenitor cells that subsequently affect Ngn2-dependent neurogenesis.